Inocybe pakistanensis, a new species in section Rimosae s. str. from Pakistan - Ullah, Zia; Jabeen, Sana; Ahmad, Habib; Khalid, Abdul Nasir (Phytotaxa, 2018)
Inocybe pakistanensis is described and illustrated as a new species based on morphological characters and molecular phylogenetic analysis of nuclear ribosomal DNA including the internal transcribed spacer (ITS) regions along with larger subunit (LSU). The distinctive basidiomata have a highly rimose and fibrillose golden brown pileus with a reddish brown, prominent umbo; ellipsoid to amygdaliform, slightly phasoeliform smooth basidiospores; and clamped septa in all the tissues. Molecular phylogenetic analysis supports the placement of I. pakistanensis in section Rimosae s. str.